Dating petroleum emplacement by illite 40Ar/39Ar laser stepwise heating: Discussion - Clauer, N.; Jourdan, Fred; Zwingmann, H. (American Association of Petroleum Geologists, 2011)
Isotopic dating of diagenetic processes in relation to hydrocarbon charge in buried sedimentary sequences is of importance to the oil industry. Yun et al. recently published in theAAPG Bulletin (v. 94,no. 6, p. 759–771) on that topic a study entitled, “Dating Petroleum Emplacement by Illite 40Ar/39ArLaser Stepwise Heating Technique.” This study raises questions about basic aspects of 40Ar/39Ardating fine-grained authigenic clay minerals, describes flawedmethodology, and ignores importantprevious work. As isotopic dating of diagenetic processes may interest readers of the AAPG Bulletinthat are not necessarily specialists in either isotopic geochronology or clay mineralogy, it appeared necessary to comment on both the technical aspects and the scientific interpretations of this study.Wediscuss especially the fact that the authors discarded 39Ar recoil followed by an evaluation of itsimpact on the results and the interpretations.